Augmentation of native microalgae based biofuel production through statistical optimization of campus sewage wastewater as low-cost growth media. Issue 5 (October 2018) - Gebremedhin, Medhanie; Mishra, Sanjeev; Mohanty, Kaustubha
Graphical abstract: Highlights: C. thermophile isolated from CSTP towards nutrient removal and biofuel production. RSM followed by SAM transformed CSTP effluent into optimal low-cost growth medium. Optimization resulted in 60% enhanced biomass yield with superior nutrient removal. TGA, FTIR, and 1 H-NMR of lipid revealed it's potential as a biofuel feedstock. Two fold increased lipid yield and FAME with 85% C16-C18 validates optimization. Abstract: The dependence of fresh-water for biomass growth is a major drawback in third generation microalgae biofuels, which need to be replaced with alternate sources. Optimizing nutrient concentrations already present in wastewater and its utilization towards microalgae growth could be a sustainable approach. In the present study, native microalga Chlorella thermophila (MF179624) was isolated and identified as model strain to optimize low-nutrient content campus sewage wastewater (CSW) using central composite design (CCD) followed by steepest ascent method (SAM). In consideration to the statistical optimization, addition of 325 mg L −1 and 1.8 g L −1 of KH2 PO4 and NaNO3 resulted in 60% enhancement of biomass yield (2.59 g L −1 ) with two fold lipid productivity (81.38 mg L −1  d −1 ). In addition, substantial nutrient removal of ammonia (98.48 ± 1.52%), nitrate (86.37 ± 3.73%), phosphate (73.83 ± 4.28%), along with COD (82.53 ± 4.37%) were achieved. Further, TGA, FTIR, and 1 H-NMR based characterization of lipid revealed its potential as a biofuel feedstock. To confirm that, two-step acid-base catalytic transesterification reaction was performed, which resulted in 474.42 mg L −1 FAME yield containing 85.14% C16 and C18.